Analisis Penerimaan Aplikasi Samsat Digital Nasional (SIGNAL) di Kota Padang Menggunakan Technology Acceptance Model (TAM) - Rahmadani Rahmadani; Iip Permana (Universitas 17 Agustus 1945, 2025)
This study is motivated by the low utilization rate of the National Digital Samsat (SIGNAL) application in Padang City, which only reached 2.1%. According to Grajek and Kretschmer (2008), a digital technology can be considered to have reached the critical mass phase when adoption rates range between 10% and 25% of the target market (Mahler & Rogers, 1999; Cool et al., 1995). Therefore, the adoption level of SIGNAL in Padang is still considered very low and has not yet entered a self-sustaining phase. This study aims to analyze the factors that influence the acceptance of the SIGNAL application using the Technology Acceptance Model (TAM). A quantitative method was applied, using data from 99 respondents analyzed through PLS-SEM with SmartPLS 4.0. The results show that Perceived Ease of Use (PEU) significantly affects both Perceived Usefulness (PU) and Attitude Toward Using (ATU), while PU does not significantly influence ATU. PU and ATU have a significant influence on Intention to Use (ITU), which subsequently affects Actual System Usage (USE). The strongest outer loading indicators were: “easy to understand” (0.854) for PEU, “improves productivity” (0.803) for PU, “rejecting alternative options” (0.861) for ATU, “motivation to continue using” (0.852) for ITU, and “user satisfaction” (0.856) for USE.